Pengaruh Harga dan Ulasan Produk terhadap Keputusan Pembelian pada Marketplace Shopee - Andrayani, Tati; Anshori, Moh. Asep Zakaria (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2024)
This research is motivated by the existence of online shopping. So that consumers, especially students, will prefer to shop online rather than having to buy products directly. Students have a tendency when choosing products with affordable prices and trusted product reviews. The purpose of this study was to test and analyze the effect of price and product reviews on purchasing decisions at the marketplace marketplace (case study of FEBI IUQI Bogor student). This type of research is quantitative. The results showed that the price variable had no partial effect on purchasing decisions, while the product review variable had a partial effect on purchasing decisions. The results of the simultaneous test show that prices and product reviews simultaneously influence purchasing decisions